World Sustainable Construction Conference - Putra Jaya, Ramadhansyah (Trans Tech Publications Ltd, 2023)
With great pleasure, we are introducing the book that collected articles from the 2022 series of World Sustainable Construction Conference (WSCC). This conference was organized by the Faculty of Civil Engineering Technology, Universiti Malaysia Pahang with support from the Universiti Sains Malaysia, Beijing Jiaotong University, Brawijaya University, Syiah Kuala University, and the University of Muhammadiyah Aceh. The World Sustainable Construction Conference was held at the Novotel Kuala Lumpur City Centre, Malaysia on the 14th and 15th of October 2022. WSCC 2022 did not fail to draw participants across the region including Malaysia, Pakistan, China, Bangladesh, Vietnam, Indonesia and Japan. The conference program was divided into three parallel sections for each day. Each presenter gave 10 minutes presentation followed by Q&A slots which lasted 5 to 10 minutes. Also, at the beginning of the parallel sessions, an hour was dedicated to each keynote presenter: Professor Dr. Ashfa Achmad, Associate Professor Dr. Ramadhansyah Putra Jaya, Dr. Eng. Tri Budi Prayogo, Dr. Khamarrul Azahari Razak, and Mr. Muhammad Helmi Abdullah. As expected, the papers submitted were more than 100 and fellow reviewers have put their heart and soul into making sure only the best quality research and technical papers were selected for presentation and publication. In line with the theme of the conference “Building Resilience”, WSCC 2022 succeeded in providing a common platform for discussions on issues, challenges, opportunities and current technologies related to the conference topic. WSCC 2022 also served as a new platform for researchers and scholars from different disciplines that have an interest in sustainable construction, agricultural technology and environmental sciences to share and discuss their research findings. There were some 100 participants including students, engineers, researchers and academicians who took part virtually and had many fruitful discussions and exchanges which again contributed to the success of this conference. Finally, on behalf of the organizing committee of WSCC 2022, we would like to thank all the presenters and participants for their great support. Last but not least, let us join our hands together in supporting and thanking our front liners battling COVID-19 pandemic.